Relationship between sprint performance and stride parameters in curved sprinting - Ishimura, K.; Tsukada, T.; Sakurai, S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the relationship between sprint performance and stride parameters in curved sprinting. Nine athletes performed 60 m maximal sprinting. Correlation coefficients between sprint time and stride parameters were calculated in three conditions, namely straight, right leg and left leg in curved sprinting separately. Significant correlations were found in contact time, step time and step frequency of right step of curved trials. The left step of curved path and straight had significant correlations in the same variables (SL and SS). Step length and step speed had significant correlations in all steps. The right step of curved path would be important for curved sprinting performance.